Occurrence of diseases and disease conditions in cattle and goats at the Upazilla Veterinary Hospital, Debidwar, Comilla - Alam, Md Badiul; Mahmud, Tareq; Khan, Shahneaz Ali; Islam, Ariful; Hai, Md Abdul; Hassan, Mohammad Mahmudul (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: A significant number of animals enrolled at UVH regularly from surrounding villages for treating their sick animals, de-worming, vaccination purposes. Therefore, a study was done to define the occurrence of common diseases and disease conditions in cattle and goats at the Upazilla Veterinary Hospital, Debidwar under Comilla district. Materials and methods: Data on various diseases were collected from the record book of hospital during April 2016 to March 2017. The total number of animals were 889, among which cattle were 637 (71.65%) and goats were 252 (28.35%). The presumptive diagnosis was performed based on general examination, physical examination, and clinical examination of animals, and microscopic examination based on common laboratory techniques. Results: Based on clinical examinations, 14 different types of diseases and disease conditions were detected. In cattle (N=637; 71.65%), where FMD (14.44%, n=92), mastitis (6.59%, n=42), digestive disorders (19%, n=121), respiratory disorders (6.12%, n=39), parasitic infestations such as mixed infestation of both ecto- and endo-parasites (34.22%, n=218), acidosis (1.88%, n=12), myiasis (6.12%, n=39), corneal opacity (1.57%, n=10), protozoal diseases (1.26%, n=8), BQ (2.20%, n=14), milk fever (0.94%, n=6), reproductive disorders (4.87%, n=31) and others (0.75%, n=5) were detected. Age wise prevalence in young and adult were (38.62%, n=246) and (61.38%, n=391), respectively. Moreover, sex wise prevalence in male and female were (34.85%, n=222) and (65.15%, n=415) respectively. In goat, (N= 252; 28.35%) 11 different types of diseases and disease conditions such as PPR (12.30%, n=31), mastitis (2.38%, n=6), digestive disorders (19.84%, n=50), parasitic infestation (29.76%, n=75), respiratory disorders (15.08, n=38), myiasis (11.11%, n=28), corneal opacity (4.76%, n=12), acidosis (1.98%, n=5) protozoal diseases such as babesiosis, anaplasmosis (0.79%, n=2) and reproductive disorders (1.59%, n=4), correspondingly. Sex wise prevalence in male and female goat were (44.05%, n=111) and (55.95%, n=141), respectively. Conclusion: All the diseases and disease conditionswere recorded more or less frequently among all age group of cattle and goats though some of the specific diseases and disease conditionshad specific age and species susceptibility such as black quarter in young cattle and PPR in young goats, respectively. A comprehensive updated data with the total population record of that area and proper analysis is needed to identify the actual level of disease and disease conditions in UVH. http://doi.org/10.5455/javar.2018.e254